Pengaruh Pembelajaran Problem Based Learning Terhadap Hasil Belajar Passing Bawah Bola Voli - Septiana Rinal Ably, Demma; Rentika Hadi, Santika; Utomo, Gatot Margisal; Mulyono (Motion: Journal Research of Physical Education, 2025)
This study aims to examine the impact of implementing the Problem-Based Learning method on improving underhand passing skills in volleyball among 11th-grade students at SMA Negeri 1 Driyorejo. The research employed a quasi-experimental approach with a pre-test and post-test design involving two groups: an experimental group and a control group. The sample consisted of 30 students, with 15 students in each group. Data analysis was conducted using a t-test with the assistance of SPSS 26 software. The findings revealed a significant improvement in underhand passing skills among students in the experimental group compared to the control group. The average post-test score of the experimental group increased from 20.90 to 27.97, with a significance level of p<0.05. These results indicate that the Problem-Based Learning method is effective in enhancing technical skills, critical thinking abilities, and student motivation